Peran ruang bagi keberlanjutan permainan tradisional anak - Dhini Dewiyanti Tantarto; Dianna Astrid Hertoery (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Playing is one of the activities naturally possessed by children from childhood and elements of learning have been observed to be in playing and vice versa. For example, traditional games have philosophical values with moral messages but they have been replaced by games prioritizing technological advancements over time. This has reduced the familiarity of many children with traditional games in recent times. Meanwhile, the reduction in the quantity and quality of play and public open space for children is often considered one of the factors causing the extinction of traditional games. The availability of an adequate environment including play areas or playground aids children's development. This paper discusses the traditional games known by the present generation and the role of space in sustaining them with the focus on West Java. The study was conducted through observation and distribution of questionnaires to children aged 6-12 years living in Bandung city and some urban settlements. The results provided an overview of the types of traditional games known by the children, the space they favored, and its role in their willingness to play. © 2020 Dhini Dewiyanti Tantarto, Dianna Astrid Hertoery